Pengembangan Media Pembelajaran Matematika Berbasis Android dalam Pembelajaran Berdiferensiasi di SMPN 1 Mantup - Adela Nur Afida Salsabila; Nur Fauziyah; Syaiful Huda (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
In differentiated learning, learning readiness is the initial ability that must be possessed by students to support the continuity of the learning process and is supported by the development of appropriate learning media. The purpose of this study was to develop differentiated mathematics learning media based on the learning readiness of android-based students named Choice Gaming with SPLDV material. This research is included in the type of Research and Development (R&D) with the Four-D model (Define, Design, Development, and Disseminate). The subjects of this study were 30 students of class VIII A SMPN 1 Mantup Lamongan. Data collection methods through instruments validation results of media experts and material experts, student response questionnaires, and pretest and posttest results. The data were analyzed using quantitative methods, obtained validity from the results of media expert validation on average 90% (very valid) and the results of material expert validation on average 86.67% (very valid). So it can be concluded that the media developed is suitable for use in learning. As for the effectiveness value obtained from the average student response of 81.67% (positive) and learning completeness obtained an average N-gain of 0.57 in the medium category (quite effective). So it can be concluded that differentiated mathematics learning media is effective for SPLDV material.